On inf-Hesitant Fuzzy Γ-Ideals of Γ-Semigroups - Pongpun Julatha; Aiyared Iampan (Advances in Fuzzy Systems)
The notions of an inf-hesitant fuzzy Γ-ideal and a sup,inf-hesitant fuzzy Γ-ideal, which are a generalization of an interval-valued fuzzy Γ-ideal, of a Γ-semigroup are introduced and some properties are investigated. Characterizations of the notions are provided in terms of sets, fuzzy sets, intuitionistic fuzzy sets, interval-valued fuzzy sets, and hesitant fuzzy sets. Furthermore, characterizations of a Γ-ideal of a Γ-semigroup are given in terms of inf-hesitant and sup,inf-hesitant fuzzy Γ-ideals.